RENTAL APPLICATION VCD / DVD RENTAL AT TALOON USING BORLAND DELPHI 7.0 - Lukman Jenri Halomoan Lumban Batu; Cut Asiana Gemawaty., Skom, MMSI Cut Asiana Gemawaty., Skom, MMSI (Jurnal Sistem Informasi, 2007)
Rental VCD / DVD rental business is engaged in VCD / DVD that require fast dataprocessing and accurately, in order to provide information about the administrativerecords of customer data and search data back old customers who have registered stillrequire quite a long time as well as loss of customer data because quite a lot of datastored.User application programs can provide results quickly, right in the tenant's dataprocessing, safe to store the data, the data report rental VCD / DVD and rentalevidence to be given to tenants. Program used in designing this application that isusing Borland Delphi 7.0.